Three new species of Ciulfina Giglio-Tos (Mantodea: Liturgusidae) from north-eastern Australia - Holwell, Gregory I.; Ginn, Scott G.; Herberstein, Marie E. (Zootaxa, 2007)
The genus Ciulfina Giglio-Tos includes a number of small tree-trunk dwelling species of praying mantids that are found through eastern Queensland and northern Australia. Three new species of Ciulfina: C. baldersoni, C. klassi and C. rentzi and one existing species C. biseriata (Westwood) are formally described on the basis of male genital morphology. A key to the identification of Ciulfina based on genital morphology is also provided.